Legal Framework of European Inland Waterways and Croatian Legislation on Inland Waterways Navigation – Problems of Non-Harmonized Rules - Biljana Činčurak Erceg (European Scientific Journal, ESJ, 2018)
Inland waterway transport, as one of the oldest modes of transport, is still under-used in the European Union. Though it has many advantages over other modes of transport (it is environmentally friendly, cost-saving, energyefficient, safety), it also faces several significant problems. The European Union has recognized the importance of inland waterway transport and has adopted several regulations establishing a legal framework for this area of transport, and has launched some programs and projects to promote it. The Republic of Croatia has harmonized its national legislation with the European, and is also the party of the most important international agreements regulating inland waterway navigation. Despite this, inland waterway navigation continues to lag behind other modes of transport. One of the reasons may be that the existing legal framework (on international, European and national level) is still not satisfactory. Further improvements, harmonization of rules and preferably unification is needed. This paper analyses the international and European legal framework as well as the Croatian legislation on inland waterway transport and makes recommendations for further changes to the existing legislation.